O07.4 The Price of Sex: Insights into the Determinants of the Price of Commercial Sex Among Female Sex Workers in Rural Zimbabwe. (13th July 2013) - Elmes, J; Nhongo, K; Hallett, T; White, P; Ward, H; Garnett, G; Nyamukapa, C; Gregson, S
Abstract : Background: Amid overall reduced demand for paid sex it is unclear how the economic organisation of sex work is affected. We explore factors associated with the price of paid sex in rural Eastern Zimbabwe. Methods: We collected and analysed cross-sectional data on 161 women who reported receiving either cash or commodities at their most recent commercial sexual encounter and who were recruited using snowball and location-based methods in October-December 2010. We used linear modelling to assess the impact of social and behavioural variables on payments for sex. Results: Eighty percent of sex workers (SW) were paid in cash; the mean payment was US11 (95% CI:9-13) and amount did not vary by payment type (p > 0.2). All acts were penile-vaginal. When clients requested condoms, consistent condom use was more prevalent than in encounters where they did not (82% vs. 38%, p < 0.01). Mean payment in 100% protected encounters was 3 lower than when condom use was inconsistent (at least one unprotected act) (p = 0.03). Mean payment was higher when encounters were initiated in private locations (SW or client's house) than in bars and public places (e.g. markets): 13, 11 and 8, respectively (trend: p = 0.003). Independent factors positively associated with payment were secondary education (vs. no or primary education, p = 0.013), a night-long encounter (vs. one act, p = 0.03), higher numbers of acts (p < 0.01), clients not requesting condoms (vs. requesting condoms, p < 0.05); encounters initiated in public (vs. private locations p < 0.01) were negatively associated with payment. Conclusion: Clients who did not request protected sex paid more than clients who did, and more educated SW were able to negotiate higher prices. Under extreme macroeconomic pressures SW may be less financially able to refuse unprotected sex. We need to understand better the importance of economics of sex work for HIV/STI epidemics.